Laparoscopic Nephroureterectomy with Heminephrectomy for Urothelial Carcinoma of the Upper Renal Pelvis on the Left Side of the Horseshoe Kidney - Taro Ikeda; Kazunori Matsumoto; Go Hasegawa; Yohei Ikeda; Noboru Hara; Tsutomu Nishiyama (Case Reports in Urology)
A 70-year-old male was diagnosed with urothelial carcinoma of the upper renal pelvis on the left side of the horseshoe kidney. Preoperative thin-slice contrast-enhanced CT with three-dimensional reconstruction of the images revealed that two arteries arising from the aorta supplied the left moiety of the horseshoe kidney. He underwent laparoscopic transperitoneal nephroureterectomy with heminephrectomy on the left side of the horseshoe kidney visualized by indocyanine green fluorescence system. The histopathological findings of the renal pelvic tumor revealed invasive urothelial carcinoma with squamous differentiation, high grade, and pT3.